1997
DOI: 10.1111/j.1440-1681.1997.tb01818.x
|View full text |Cite
|
Sign up to set email alerts
|

Mediators on Human Airway Smooth Muscle

Abstract: 1. Bronchial hyperresponsiveness in asthma may be due to several abnormalities, but must include alterations in the airway smooth muscle responsiveness and/or volume. 2. Increased responsiveness of airway smooth muscle in vitro can be induced by certain inflammatory cell products and by induction of sensitization (atopy). 3. Increased airway smooth muscle growth can also be induced by inflammatory cell products and atopic serum. 4. Mast cell numbers are increased in the airways of asthmatics and, in our studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In addition to the increased presence of immunoregulatory cells, asthmatics experience structural airway remodeling including increases in size and number of mucoussecreting globular cells and variable increases in wall thickness (19). Additionally, smooth muscle hyperplasia may occur in the airways increasing the smooth muscle area by up to three times (6). Inflammation and remodeling of the airways contribute to bronchial hyperresponsiveness, an exaggeration of the bronchoconstrictor response to pathogens or other stimuli contacting the airway epithelium (26).…”
Section: Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the increased presence of immunoregulatory cells, asthmatics experience structural airway remodeling including increases in size and number of mucoussecreting globular cells and variable increases in wall thickness (19). Additionally, smooth muscle hyperplasia may occur in the airways increasing the smooth muscle area by up to three times (6). Inflammation and remodeling of the airways contribute to bronchial hyperresponsiveness, an exaggeration of the bronchoconstrictor response to pathogens or other stimuli contacting the airway epithelium (26).…”
Section: Asthmamentioning
confidence: 99%
“…Inflammation and remodeling of the airways contribute to bronchial hyperresponsiveness, an exaggeration of the bronchoconstrictor response to pathogens or other stimuli contacting the airway epithelium (26). Together, airway inflammation, remodeling, hyperresponsiveness, and possible airway edema contribute to overall airway narrowing (6,19).…”
Section: Asthmamentioning
confidence: 99%
“…A irway smooth muscle (ASM) 3 cells are key determinants of asthma due to their ability to contract in response to inflammatory cell products (1,2). Due to intrinsic phenotype plasticity, airway myocytes exhibit a capacity for multifunctional behavior and contribute to local inflammation and fibrosis (3).…”
mentioning
confidence: 99%
“…We assessed the potential role of 8‐epi‐PGF 2 α in cholinergic responsiveness by adding a subthreshold concentration in the organ bath prior to constructing a dose–response curve to ACh. As it has been shown that the addition of inflammatory mediators to the organ bath solution increases the responsiveness to ACh of isolated bronchial rings from healthy humans (Jongejan et al ., 1990; Armour et al ., 1997), it was speculated that 8‐epi‐PGF 2 α would act in a similar way in equine bronchi. But neither in healthy nor in heaves‐affected horses was the response (E max and pD 2 ) to ACh enhanced by addition of 8‐epi‐PGF 2 α (Table 2).…”
Section: Discussionmentioning
confidence: 99%